Kualitas Pelayanan Publik Pada PLN Mobile - Marlina Isna Nur Aulia; Muhammad Dzikri Mustopa; Mutiara Zulfa (UIN Sunan Gunung Djati Bandung, 2024)
Technological advances provide benefits in public services to the community, especially at PT. PLN (Persero). Utilization of technology with good quality can provide satisfaction for the community itself. This research is entitled